Effect of Organic Sources of Nutrients on Flowering Characters and Yield of Strawberry (Fragaria ananassa Duch) cv. Douglas - Tudu, Sushila; Misra, Sanyat; Rashmita; Shanker, Karuna (International Journal of Bio-resource and Stress Management, 2023)
An experiment was carried out at Birsa agricultural university to evaluate the effect of different organic sources of nutrients on flowering characters and yield parameters of strawberry (Fragaria ananassa Duch) cv. Douglas during season i.e. October 2012 and April 2013 in Ranchi conditions under chhotanagpur plateau region of Jharkhand. The experiment comprised of thirteen treatments with organic manures, biofertlizers and their combinations along with the recommended dose of fertilizers the treatment were laid out in randomized block design with three replications each. The minimum number of days taken for first flowering (101.00 days), maximum Number of flowers (27.45), Length of flower stalk (13.95 cm), minimum number of days taken to fruit set (4.13 days) was recorded with treatment FYM (7.5 t ha-1)+vermicompost (3.18 t ha-1) +PSB (5 kg ha-1)+Azotobacter (5 kg ha-1). The same treatment also recorded maximum number of fruits plant-1 (19.66), Yield plant-1 (0.166 kg), Yield plot-1 (6.00 kg), Yield ha-1 (66.66 q) was recorded with FYM (7.5 t ha-1)+vermicompost (3.18 t ha-1)+PSB (5 kg ha-1)+Azotobacter (5 kg ha-1). Treatments FYM (10 t ha-1)+vermicompost (4.25 t ha-1), vermicompost (6.37 t ha-1)+PSB (5 kg ha-1)+Azotobacter (5 kg ha-1), RDF 100:60:60 NPK (kg ha-1) were all statistically at par with FYM (7.5 t ha-1)+vermicompost (3.18 t ha-1)+PSB (5 kg ha-1)+Azotobacter (5 kg ha-1) for most of the flowering, yield and yield attributing characters and hence, can also be tried for obtaining higher yield of fruits in strawberry.